2018
DOI: 10.1080/01480545.2018.1424179
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol, a plant-derived phenolic nutraceutical, protects thiol (SH) group in myocardium from ROS-mediated oxidation under chemotherapeutic stress induced by arsenic trioxide – ain vivomodel study

Abstract: Arsenic trioxide is an effective chemotherapeutic agent for the treatment of acute promyelocytic leukemia. The clinical usefulness of arsenic trioxide is narrow due to different organ toxicities. It is hypothesized that the generation of reactive oxygen species by arsenic trioxide leads to thiol-based oxidative damage in rat myocardium. In this study, the defensive effect of eugenol on thiol-based oxidative stress was investigated in arsenic trioxide-treated rats. Rats were orally administered with arsenic tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Reportedly, polyphenol-rich plants and polyphenolic compounds, such as flavonoids, carotenoids, and phenolic acid, exhibit protective effects against oxidative stress-induced hepatotoxicity by either the direct scavenging of ROS or the modulation of endogenous antioxidant defense system [ 21 , 22 , 23 ]. More recently, a study was conducted to elucidate the profile of phytochemical constituents in 20 different lentil cultivars and their antioxidant activities, and the results revealed that the content of total tocopherols and total carotenoids were 37–64 μg/g dry weight (DW) and 5.3–28.1 μg/g DW, respectively [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reportedly, polyphenol-rich plants and polyphenolic compounds, such as flavonoids, carotenoids, and phenolic acid, exhibit protective effects against oxidative stress-induced hepatotoxicity by either the direct scavenging of ROS or the modulation of endogenous antioxidant defense system [ 21 , 22 , 23 ]. More recently, a study was conducted to elucidate the profile of phytochemical constituents in 20 different lentil cultivars and their antioxidant activities, and the results revealed that the content of total tocopherols and total carotenoids were 37–64 μg/g dry weight (DW) and 5.3–28.1 μg/g DW, respectively [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Binu et al [28] showed that eugenol restored liver function from arsenic-induced liver injury. Further, the antioxidant effects of eugenol have been highlighted in various disease models, proving its versatility [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Synthetic or natural scavengers of ROS and antioxidants could attenuate ATO-induced toxicity, thereby enabling full exploitation of the therapeutic potential of ATO. 15 The imbalance between the generation of ROS and the antioxidant systems is usually maintained by critical enzymes, for example, superoxide dismutase (SOD) and catalase (CAT). 13 Exposure of arsenic to individuals involved in the production of pro-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%